THE INFLUENCE OF GRAMMAR AND VOCABULARY MASTERY TOWARD WRITING ABILITY IN THE SECOND SEMESTER STUDENTS OF ENGLISH DEPARTMENT - Khilda Husnia Abidah; Kurniasih Kurniasih; Dzurriyyatun Ni'mah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
The aim of this study is to find out whether or not there is influence between students’ grammar and vocabulary mastery toward their writing ability. The subject of this study was 45 second semester students of English Department in which are reviewing about the topic of writing material. The data were collected using tests of grammar, vocabulary, and also writing. The result of this study showed that Fo (5.491) at Sig. 0.008 in which it is smaller than 0.01. It means that students’ grammar and vocabulary mastery, simultaneously, influenced significantly toward their writing ability. Furthermore, from both independent variables which gave contribution toward writing ability, grammar mastery contributed 0.107 (10.7%) and vocabulary mastery contributed 0.182 (18.2%) while 71.1% are contributed by other factors. It means that vocabulary mastery has higher contribution toward writing ability than grammar mastery. Therefore, based on these findings, it is suggested for the English teacher to emphasize on using correct grammar and appropriate vocabulary during producing text, and also drilled the students to write either academic or non-academic writing so that the students are able to use grammar and vocabulary. However, it is also suggested for further researcher to develop this study by investigating another independent variables which gave higher contribution toward writing abilityKeywords: grammar mastery, vocabulary mastery, writing ability, influence